Pendampingan Pastoral terhadap Orang yang Berduka Karena Kehilangan Bapak Akibat Kecelakaan - risma, siregar (JURNAL DIAKONIA, 2021)
Grief is a human reaction to defend one self when faced with loss events such as death, separation, or the loss of something valueable that affects aspects of human life holistically.The level of human sadnessis influenced by the value of the lost object, the emotional connection with the lost object, the period of loss of the object, the form of the lost object, the number of lost object, the level of anticipation of loss and the social support system. This studi aims to determine the level of sadness experieirnced by the client (PS) due to the loss of a father due to an accident in the village X Balige. Greaf experienced by the client, including prolonged grief. Seventeen year ago until now, she had not been able to manage has grief, her conditions was unstable. Therefore, the author conducts research and help through assistance, so that mourners healing, realize and acceptance.